The effect of FeCI3 on changes in the rheological properties of glycerol determined by an acoustic method - WACIŃSKI, Marek; PŁOWIEC, Ryszard (Archives of Acoustics, 2016)
The results of the shear mechanical impedance measurements are presented for solutions of FeCI3 in glycerol at frequencies 30 and 500 MHz and over a temperature range from 218-303 K. These results complemented the previous investigations [4] performed at a frequency of 0.5 MHz. A distinct effect of FeC13 on the range of the viscoelastic relaxation of glycerol and on its molecular structure was found.